Relics of the Body-Snatchers: Supplementary Notes on Mortsafe Tackle, Mortsafes, Watch-houses, and Public Vaults, mostly in Aberdeenshire (Proceedings of the Society of Antiquaries of Scotland, 1921)
The paper describe mortsafe tackle at Inverurie, mortsafes at Oyne and Auchlossan, watch-houses at Nigg and Dyce, and public vaults at Culsalmond and Marnoch. The mortsafes which were so frequently in use about a century ago were intentionally made very heavy to prevent their removal or destruction by unauthorised persons who might wish to gain access to the bodies they protected. Therefore for lowering them into position in the grave at the time of burial, and for lifting them out again when all danger of body-snatching was past, strong tackle was required. Auchlossan possesses two mortsafes, both of the iron, coffin-shaped variety. The mortsafe at Oyne had not been constructed for the use of the public, but was made for a single private burial, and this accounted for its somewhat weak construction. In the corner of the churchyard at Nigg there is a small building formerly used as a watch-house, but now kept as a storeroom for the tools required by the gravedigger. A watch-house was erected in the south-east corner of the churchyard at Dyce. At Culsalmond a two-storied building stands in the north-west corner of the churchyard. Its lower portion consists of a vault which was built for the purpose of storing coffins in safety till the bodies they contained were useless for anatomical purposes. In the churchyard of Marnoch, Banffshire, there is a vault, almost entirely underground, over which a second story has been built like that at Culsalmond. A flight of ten steps leads down to the entrance, just above which a stone tablet has been built into the wall, bearing the words " Built by Subscription in the year 1832. Addition 1877."